Horizontal and vertical emissions of methane from peat soils: Methane emission from peat soils (Journal of the Bangladesh Agricultural University, 2019)
Methane emission depends on the rates of methane production, consumption and ability of soil and plants to transport the gas to the soil surface and also within soil particles. The objective of this study was to determine CH4 fluxes horizontally and vertically from the floor and wall of the pit of a tropical peat soil. The horizontal emissions in the dry and wet seasons were 2.96 t CH4 ha-1yr-1 and 4.27 t CH4 ha-1yr-1, respectively and the vertical emissions were 0.36 t CH4 ha-1yr-1 and 0.51 t CH4 ha-1yr-1, respectively. The total amount of the horizontal and vertical emissions in the dry and wet seasons were 3.32 t CH4 ha-1yr-1 and 4.78 t CH4 ha-1yr-1, respectively. Horizontal emission was higher in the wet season due to an increase in the water table which resulted in an increase of CH4 emission. Thus, there is a need for direct CH4 measurement from cultivated peat soils to ensure that CH4 emission is neither underestimated nor overestimated.J Bangladesh Agril Univ 17(3): 359–362, 2019